آليات اعتماد برنامج إنمائي فعال في التنمية المستدامة - حاج, تقي الدين; عوادي, عبد القادر; قويدر, محمد الطيب (جامعة الوادي - University of Eloued, 2018)
تعرف التنمية المستدامة بأنها التنمية التي تلبي احتياجات الجيل الحاضر دون التضحية أو المساس أو الأضرار بحق وقدرة الأجيال القادمة على تلبية احتياجاتهم للبقاء على قيد الحياة" وهذا يعني أن التنمية المستدامة تهدف إلى تلبية حاجات الجيل الحالي من دون تفريط أو الإهمال في حاجات الجيل اللاحق ومن خلال هذا التعاريف أمكننا القول أن التنمية المستدامة تسعى لتحقيق نوعية لحياة الإنسان واستغلال الموارد الطبيعية بطريقة عقلانية ومحاولة إبقائها لمدة زمنية بعيدة، وضمان متطلبات الأجيال المقبل . إلا أن التحول نحو الاستدامة المنشودة لا يبدو ممكنا بدون حدوث تغير رئيس وجذري على مستوى النموذج المعرفي بحيث يراعي خصوصية الأنساق الثقافية للمجتمعات، بغية تطبيق برامج تنموية تناسب طبيعة كل مجتمع، كذلك لا بد من برامج تنموية تشرك الإنسان، ولا تهمله بالاعتماد على موارد الطبيعة فقط، وينبغي مواءمة الخطط التنموية بحيث تتوافق وقيم ومثل الإنسان، حتى تجعل هدف حركته وإشراكه في التنمية، ليس ذا بعد مادي وأرضي فقط، بل ذا بعد معنوي، الأمر الذي يضمن استقطاب أكبر عدد من الطاقات الإنسانية، بل ويكون البذل في الجهد مضاعفا . فان أي تنمية مستدامة لا تضع برامجها وفق قيم المجتمع، فمصيرها الفشل، والعكس يضمن تحقيق النمو، والإبداع، والتعاون، بدل التنافس،والاحتكار لأن دافع الحركة ليس مادي فقط بل سماوي، الأمر الذي يشعر كل فرد بالاطمئنان من صحة نشاطه في ظل قيمه فيتضاعف مردوده وجودة أداءه، وبهذا الشكل يمكن الحديث عن تنمية مستدامة حقيقية، تقضي على الفقر والجوع وتضمن النهضة الشاملة. Sustainable development is defined as development that meets the needs of the present generation without sacrificing, compromising or harming the right and ability of future generations to meet their survival needs. However, the shift towards sustainability does not seem possible without a fundamental and radical change at the cognitive level to take into account the specificity of the cultural patterns of societies in order to implement development programs that are appropriate to the nature of each society. There is also a need for development programs that involve people, not only by relying on the natural resources, and those development plans should be adapted to the values and ideals of man, so as to make the goal of his movement and involvement in development not only having a physical and earthly dimension, but a moral dimension too, which ensures the polarization of the largest number of human energies doubled. It is agreed that any sustainable development which does not put its programs according to the values of society is doomed to failure. Taking into account this aspect, however, ensures growth, creativity, cooperation, competition rather than monopoly because the motive of the movement is not only physical but heavenly, which makes everyone feel reassured by the validity of his activity in light of the value of his/her morals and the quality of performance, and as such, we can address real sustainable development which is able at eradicating poverty and hunger and ensuring the comprehensive renaissance.
مقال
Keywords: الآلية، التنمية المستدامة، البرنامج . Mechanism – Sustainable Development - Development Programming